Key features of alumina/magnesia/graphite refractories for steel ladle lining - Resende, W. S.; Gomes, J. E.; Varela, José Arana [UNESP]; Stoll, R. M.; Justus, S. M.; Andrade, R. M.; Longo, Elson [UNESP]; Baldo, J. B.; Leite, E. R.; Paskocimas, C. A.; Soledade, L. E B (Elsevier, 2000)
The corrosion resistance of resin bonded alumina/magnesia/graphite refractories containing different kinds of aggregates were investigated when submitted to the action of slags of several CaO/SiO2 ratios. The laboratory testing was performed by means of the rotary slag attack test. Specifically evaluated was the influence of alumina/carbon ratio and magnesia and silica contents on the refractories corrosion resistance. It was found that this property could be improved by increasing the refractory Al2O3/SiO2 ratio as well as by choosing the appropriate Al2O3/C ratio. © 2000 Elsevier Science Ltd.
Keywords: Al2O3/MgO/C; Refractories; Slag resistance; Steel ladle lining; Alumina; Corrosion resistance; Graphite; Ladle metallurgy; Lime; Magnesia; Silica; Slags; Steel metallurgy; Ceramic materials